2022
DOI: 10.3390/ijms23052469
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Human Somatic piRNA Expression in Parkinson’s Disease Subtypes and Stages

Abstract: Piwi interacting RNAs (piRNAs) are small non-coding single-stranded RNA species 20–31 nucleotides in size generated from distinct loci. In germline tissues, piRNAs are amplified via a “ping-pong cycle” to produce secondary piRNAs, which act in transposon silencing. In contrast, the role of somatic-derived piRNAs remains obscure. Here, we investigated the identity and distribution of piRNAs in human somatic tissues to determine their function and potential role in Parkinson’s disease (PD). Human datasets were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 149 publications
(158 reference statements)
0
12
0
Order By: Relevance
“…Zhang and Wong detected 296 and 508 out of 902 somatic piRNAs in the prefrontal cortex and amygdala that is a frequent site of Lewy bodies, respectively, of which, 20 and 55 piRNAs were differentially expressed in PD ( Zhang and Wong, 2022 ; Table 1 ). They further found that 55 piRNAs that were differentially expressed in the amygdala of patients with PD were predicted to target 20 protein-coding genes, including Mitochondrially encoded cytochrome C oxidase I ( MT-CO1 ) and MT-CO3 ( Zhang and Wong, 2022 ), which encode the protein components of respiratory complex IV of the electron transport chain and are implicated in PD ( Bartels and Leenders, 2010 ; Foti et al, 2019 ; Choong et al, 2021 ). In addition, changes in piRNA expression levels were also observed in different PD stages and subtypes, such as the premotor and motor stages of PD and Parkinson’s disease dementia (PDD), a PD-associated dementia ( Goldman and Postuma, 2014 ; Weil et al, 2017 ), suggesting the possible involvement of piRNAs in the onset and progression of PD ( Zhang and Wong, 2022 ).…”
Section: Pirna and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Wong detected 296 and 508 out of 902 somatic piRNAs in the prefrontal cortex and amygdala that is a frequent site of Lewy bodies, respectively, of which, 20 and 55 piRNAs were differentially expressed in PD ( Zhang and Wong, 2022 ; Table 1 ). They further found that 55 piRNAs that were differentially expressed in the amygdala of patients with PD were predicted to target 20 protein-coding genes, including Mitochondrially encoded cytochrome C oxidase I ( MT-CO1 ) and MT-CO3 ( Zhang and Wong, 2022 ), which encode the protein components of respiratory complex IV of the electron transport chain and are implicated in PD ( Bartels and Leenders, 2010 ; Foti et al, 2019 ; Choong et al, 2021 ). In addition, changes in piRNA expression levels were also observed in different PD stages and subtypes, such as the premotor and motor stages of PD and Parkinson’s disease dementia (PDD), a PD-associated dementia ( Goldman and Postuma, 2014 ; Weil et al, 2017 ), suggesting the possible involvement of piRNAs in the onset and progression of PD ( Zhang and Wong, 2022 ).…”
Section: Pirna and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Moreover, the expression levels of six piRNAs, piR-has-92056 , piR-hsa-150797 , piR-hsa-347751 , piR-hsa-1909905 , piR-hsa-2476630 , and piR-hsa-2834636 in blood small extracellular vesicles showed the highest relevance to PD, with an AUC value of 0.89 using a sparse partial least square discriminant analysis (sPLS-DA), suggesting that these piRNAs can be potential noninvasive biomarkers for PD diagnosis ( Zhang and Wong, 2022 ).…”
Section: Pirna and Neurodegenerative Diseasesmentioning
confidence: 99%
“…They are primarily expressed in the testes and ovaries of mammals and are essential for germline development and fertility [9]. The dysregulation of piRNAs has been associated with various diseases [10,11] , including cancer [12], where they can influence gene expression in somatic cells [13]. It is also known that many piRNAs are dysregulated in tumor 2 tissues, where they can either promote or suppress tumor growth [14].…”
Section: Introductionmentioning
confidence: 99%
“…PiRNAs are also involved in various neurological processes, including cognition, learning, and memory-related behaviors [ 21 , 22 , 23 ]. What is more, dysregulation of the piRNAs/PIWI pathway is linked to neurodevelopmental and degenerative diseases [ 24 , 25 , 26 , 27 ]. For example, in two Parkinson’s disease Caenorhabditis elegans models, 21ur-10824 , 21ur-11898 , and 21ur-13215 are significantly up-regulated in both α-syn(A53T) Tg and Aβ Tg and α-syn(A53T) Tg transgenic strains [ 28 ].…”
Section: Introductionmentioning
confidence: 99%